CORM-401 Reduces Ischemia Reperfusion Injury in an Ex Vivo Renal Porcine Model of the Donation After Circulatory Death. Issue 7 (July 2018) - Bhattacharjee, Rabindra N.; Richard-Mohamed, Mahms; Sun, Qizhi; Haig, Aaron; Aboalsamh, Ghaleb; Barrett, Peter; Mayer, Richard; Alhasan, Ibrahim; Pineda-Solis, Karen; Jiang, Larry; Alharbi, Hajed; Saha, Manujendra; et al.
Abstract : Background: Carbon monoxide (CO) inhalation protects organ by reducing inflammation and cell death during transplantation processes in animal model. However, using CO in clinical transplantation is difficult due to its delivery in a controlled manner. A manganese-containing CO releasing molecules (CORM)-401 has recently been synthesized which can efficiently deliver 3 molar equivalents of CO. We report the ability of this anti-inflammatory CORM-401 to reduce ischemia reperfusion injury associated with prolonged cold storage of renal allografts obtained from donation after circulatory death in a porcine model of transplantation. Methods: To stimulate donation after circulatory death condition, kidneys from large male Landrace pig were retrieved after 1 hour warm ischemia in situ by cross-clamping the renal pedicle. Procured kidneys, after a brief flushing with histidine-tryptophan-ketoglutarate solution were subjected to pulsatile perfusion at 4°C with University of Wisconsin solution for 4 hours and both kidneys were treated with either 200 μM CORM-401 or inactive CORM-401, respectively. Kidneys were then reperfused with normothermic isogeneic porcine blood through oxygenated pulsatile perfusion for 10 hours. Urine was collected, vascular flow was assessed during reperfusion and histopathology was assessed after 10 hours of reperfusion. Results: We have found that CORM-401 administration reduced urinary protein excretion, attenuated kidney damage markers (kidney damage marker-1 and neutrophil gelatinase-associated lipocalin), and reduced ATN and dUTP nick end labeling staining in histopathologic sections. CORM-401 also prevented intrarenal hemorrhage and vascular clotting during reperfusion. Mechanistically, CORM-401 appeared to exert anti-inflammatory actions by suppressing Toll-like receptors 2, 4, and 6. Conclusions: Carbon monoxide releasing molecules-401 provides renal protection after cold storage of kidneys and provides a novel clinically relevant ex vivo organ preservation strategy. Abstract : The authors demonstrate that perfusate infused CORM-401 protects the kidney from postreperfusion injury through reduction of vascular resistance, apoptosis and necrosis in a porcine DCD model.